A DFT study of the mechanism and selectivities of the [3 + 2] cycloaddition reaction between 3‐(benzylideneamino)oxindole and trans‐β‐nitrostyrene. (9th September 2016) - Sobhi, Chafia; Khorief Nacereddine, Abdelmalek; Djerourou, Abdelhafid; Ríos‐ Gutiérrez, Mar; Domingo, Luis R.
Abstract : The mechanism and regioselectivities and stereoselectivities of the [3 + 2] cycloaddition (32CA) reaction of 3‐(benzylideneamino) oxindole (AY) and trans ‐β‐nitrostyrene have been studied using both B3LYP and ωB97XD density functional theory methods together with the standard 6‐31G(d) basis set. Four reactive pathways associated with the ortho and meta regioselective channels and endo and exo stereoselective approaches modes have been explored and characterized. While the B3LYP functional fails to predict the experimental regioselectivity, the ωB97XD one succeeds to predict the experimentally observed meta regioselectivity favoring the formation of meta / endo cycloadduct as the major isomer. Inclusion of solvent effects increases the regioselectivity and decreases the experimentally observed stereoselectivity. Analysis of the density functional theory global reactivity indices and the Parr functions of the reagents in its ground state allows explaining the reactivity and the meta regioselectivity of this zwitterionic‐type 32CA reaction, which account for the high polar character of this reaction. Non‐covalent interaction analysis of the most favorable meta / endo transition state structure reveals that the formation of a hydrogen‐bond between 1 nitro oxygen and the AY N–H hydrogen is responsible for the selectivity experimentally found in this polar zwitterionic‐type 32CA reaction. Abstract : In this work is a theoretical study of a cycloaddition reaction of an azomethine ylide with nitrostyrene using ωB97XD density functional theory methods, in which we have found that it takes place through one‐step asynchronous TS with a polar character and very low activation energy. The formation of a hydrogen bond between one of the two nitro oxygen atoms and the N ‐ylide hydrogen one accounts for the endo selectivity found in this cycloaddition reaction. The Parr functions predict a meta regioselectivity for this cycloaddition reaction, in agreement with the experimental observations.